Graphene–Mesoporous Si Nanocomposite as a Compliant Substrate for Heteroepitaxy. Issue 18 (15th March 2017) - Boucherif, Abderrahim Rahim; Boucherif, Abderraouf; Kolhatkar, Gitanjali; Ruediger, Andreas; Arès, Richard
Abstract : The ultimate performance of a solid state device is limited by the restricted number of crystalline substrates that are available for epitaxial growth. As a result, only a small fraction of semiconductors are usable. This study describes a novel concept for a tunable compliant substrate for epitaxy, based on a graphene–porous silicon nanocomposite, which extends the range of available lattice constants for epitaxial semiconductor alloys. The presence of graphene and its effect on the strain of the porous layer lattice parameter are discussed in detail and new remarkable properties are demonstrated. These include thermal stability up to 900 °C, lattice tuning up to 0.9 % mismatch, and compliance under stress for virtual substrate thicknesses of several micrometers. A theoretical model is proposed to define the compliant substrate design rules. These advances lay the foundation for the fabrication of a compliant substrate that could unlock the lattice constant restrictions for defect‐free new epitaxial semiconductor alloys and devices. Abstract : A graphene–porous silicon nanocomposite is proposed for a novel concept of tunable compliant substrate for epitaxy, which extends the range of available lattice constants for epitaxial semiconductor alloys. Remarkable properties are demonstrated experimentally: thermal stability up to 900 °C, lattice tuning of at least 0.9% mismatch, and compliance under stress. A theoretical model is proposed to define the compliant substrate design rules.